2021
DOI: 10.1136/bcr-2020-240178
|View full text |Cite
|
Sign up to set email alerts
|

Late onset of Guillain-Barré syndrome following SARS-CoV-2 infection: part of ‘long COVID-19 syndrome’?

Abstract: We describe a case of delayed onset, acute demyelinating neuropathy secondary to novel SARS-CoV-2 infection. A previously healthy 46-year-old man presented with bilateral leg pain and loss of sensation in his feet 53 days after having COVID-19 pneumonitis. He developed painful sensory symptoms followed by a rapidly progressive lower motor neuron weakness involving all limbs, face and respiratory muscles, needing ventilatory support. In keeping with a diagnosis of Guillain-Barré syndrome, cerebrospinal fluid ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0
5

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(44 citation statements)
references
References 21 publications
0
39
0
5
Order By: Relevance
“…One case was excluded as it met one of the exclusion criteria; the latency between the onset of COVID-19 infection and the GBS onset of symptoms was 53 d (>6 weeks). 93 The applied investigations in confirming COVID-19 infection at the time of arboviral symptoms were COVID-19 PCR testing, detection of SARS-CoV2 antibodies, and suggestive features on chest radiography. Cases with either positive PCR or SARS-CoV2 antibodies were categorized as confirmed cases, whereas patients diagnosed based on abnormal chest radiographs or clinical suspicion only were categorized as suspected cases.…”
Section: Resultsmentioning
confidence: 99%
“…One case was excluded as it met one of the exclusion criteria; the latency between the onset of COVID-19 infection and the GBS onset of symptoms was 53 d (>6 weeks). 93 The applied investigations in confirming COVID-19 infection at the time of arboviral symptoms were COVID-19 PCR testing, detection of SARS-CoV2 antibodies, and suggestive features on chest radiography. Cases with either positive PCR or SARS-CoV2 antibodies were categorized as confirmed cases, whereas patients diagnosed based on abnormal chest radiographs or clinical suspicion only were categorized as suspected cases.…”
Section: Resultsmentioning
confidence: 99%
“…At a longer follow-up of 6 months, Pilotto et al, analyzing retrospectively 165 moderate-to-severe COVID-19 patients, showed that these long-term symptoms persisted in about 37% of patients (61). Also, symptoms consistent with orthostatic hypoperfusion syndrome and painful small fiber neuropathy were reported at short (3 weeks) and long (up to 3 months) follow-ups in two case-reports and in a small case-series (48,59,63). In a "Long-Haul COVID" communication, Nath et al, summarizing symptoms reported after mild-to-severe COVID-19, also highlighted persistent symptoms that overlapped with those patients with myalgic encephalomyelitis/chronic fatigue syndrome (117).…”
Section: Persistent Neurological Symptoms and Olfactory Dysfunctionsmentioning
confidence: 99%
“…Furthermore, our patient presented with an AMSAN, whereas the majority of reported cases present with a demyelinating polyradiculoneuropathy [ 1 , 6 , 7 ]. A previous case report details late onset GBS 53 days following SARS-CoV-2 infection [ 8 ]. Our patient demonstrated a distinctly longer latency period between COVID-19 symptoms and GBS than previously reported cases.…”
Section: Discussionmentioning
confidence: 99%